PENGAKUAN HAK ULAYAT DAN PARADOKS KETAHANAN PANGAN DI INDONESIA: KRITIK NORMATIF ATAS FOOD ESTATE DAN KEADILAN TENURIAL - Rahmadani Rahmadani; Rosdiani Azis (Indonesian Journal of Legality of Law, 2026)
Artikel ini menganalisis paradoks pengakuan hak ulayat masyarakat adat dalam kebijakan ketahanan pangan di Indonesia, khususnya ketika agenda food estate dan ekspansi pangan berbasis lahan skala besar beririsan dengan wilayah adat. Secara normatif, hak ulayat telah memperoleh dasar pengakuan melalui Pasal 18B ayat (2), Pasal 28I ayat (3), dan Pasal 33 UUD 1945, Pasal 3 Undang-Undang Pokok Agraria, serta Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 yang menegaskan bahwa hutan adat bukan hutan negara. Namun, pengakuan tersebut belum sepenuhnya menjamin perlindungan substantif karena masyarakat adat masih menghadapi fragmentasi regulasi, tumpang tindih izin, lambannya pengakuan administratif, lemahnya pelaksanaan free, prior and informed consent (FPIC), serta dominasi paradigma pembangunan pangan yang menempatkan tanah sebagai faktor produksi. Artikel ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan kontekstual-kasus. Analisis dilakukan melalui dua tahap, yaitu analisis koherensi normatif terhadap pengakuan hak ulayat dalam kebijakan food estate, dan analisis preskriptif-rekonstruktif untuk merumuskan model ketahanan pangan berbasis keadilan tenurial. Hasil kajian menunjukkan bahwa food estate berpotensi menciptakan paradoks konstitusional: negara mengejar ketahanan pangan nasional, tetapi pada saat yang sama berisiko melemahkan ketahanan pangan masyarakat adat melalui konversi ruang hidup, hilangnya pangan lokal, dan terganggunya sistem ekologis adat. Artikel ini menegaskan bahwa hak ulayat bukan hambatan bagi pembangunan pangan, melainkan prasyarat bagi ketahanan pangan yang adil, berkelanjutan, dan sesuai dengan keadilan konstitusional. This article analyzes the paradox of the recognition of Indigenous Peoples’ customary land rights within Indonesia’s food security policy framework, particularly where food estate initiatives and large scale land based agricultural expansion intersect with customary territories. Normatively, customary land rights have been constitutionally and legally recognized through Article 18B paragraph (2), Article 28I paragraph (3), and Article 33 of the 1945 Constitution of the Republic of Indonesia, Article 3 of the Basic Agrarian Law, as well as Constitutional Court Decision No. 35/PUU-X/2012, which affirmed that customary forests are not state forests. Nevertheless, such recognition has not yet ensured substantive protection, as Indigenous communities continue to face regulatory fragmentation, overlapping land use permits, protracted administrative recognition processes, inadequate implementation of the principle of Free, Prior and Informed Consent (FPIC), and the predominance of a food development paradigm that treats land primarily as a factor of production. This study employs a normative legal research method, utilizing statutory, conceptual, and contextual case approaches. The analysis is conducted in two stages: first, a normative coherence analysis of the recognition of customary land rights within food estate policies; and second, a prescriptive reconstructive analysis aimed at formulating a food security model grounded in tenure justice. The findings reveal that food estate development may generate a constitutional paradox: while the state seeks to strengthen national food security, it simultaneously risks undermining the food security of Indigenous communities through the conversion of customary living spaces, the erosion of local food systems, and the disruption of customary ecological structures. This article argues that customary land rights should not be perceived as an obstacle to food development. Rather, they constitute a fundamental prerequisite for achieving food security that is equitable, sustainable, and consistent with the principles of constitutional justice.